The National identity in Kurdish proverbs (Raparin Journal of Humanities (RJH), 2024)
Identity is intimately related to people’s understanding of “who they are,” “what they are,” and what matters to them. This understanding depends on a number of factors. Identity also creates similarities and differences between individuals or groups. In fact, the emergence of identity is the emergence of similarities and differences between oneself and the other. That is, when someone says I am that person, that family, that nation, he says I am different from this and that and the others.  National identity is an individual's sense of affiliation with a nation. Geography has its impact on language and national identity. Without this geography, called the country, states, cultures and civilizations could not exist. Lifestyles, forms of communication and languages have emerged according to the areas in which people live.  This research is entitled “National Identity in Kurdish Proverbs”. Through the study of the content of Kurdish folk proverbs, many of the characteristics of the national identity and civilizational characteristics of an important part of the population of Kurdistan, especially in the center and south, can be known. This includes familiarity with the customs and traditions and the nature of the economic, social and political situation. This research is an attempt to get to know the Kurds through the Kurds themselves, not foreigners. This paper aims to demonstrate this role. The aim of this study is to show the role and characteristics of proverbs as some examples of oral means of expressing Kurdish national identity, because proverbs are the wisdom of human experience and a mirror of culture, opinions, norms and lifestyles. For this purpose, the method of "descriptive, analytical" has been used to interpret the content of the proverbs that carry national identity.